Genetic basis of human disorders of gonadal development - Maison, Patrick Opoku Manu (Division of Urology, 2018)
South Africa is unique in the arena of Intersex, in that for unknown reasons we have a very high percentage of ovotesticular DSD (True Hermaphrodite). Whereas ovotesticular DSD is the least common cause of hermaphroditism in other parts of the world, it is the most common cause of hermaphroditism in South Africa. There have been several studies in the past to determine the cause of ovotesticular DSD in our population but none of these studies found appropriate answers. The current state of understanding implicates signaling and signal transduction molecules and transcription factors suggesting that it is likely not all of the genetic factors involved have already been identified. It was hypothesized that exome sequencing of individuals with DGDs will identify new mutations and genes for these conditions. Therefore, this study aims to identify additional genes that are associated with ovotesticular DSD. By using a whole-genome sequencing approach we expected to be able to identify rare variants with this condition and determine the prevalence of mutations in these genes in the ovotesticular DSD population. After obtaining informed consent, blood specimen was obtained from eleven out of fifteen patients who had histological diagnosis of Ovotesticular DSD at the Red Cross War Memorial Hospital over a 10 year period. Blood specimen was also obtained from the biological parents of these children and sent to the Ostrer laboratory for whole genome sequencing and analysis. At the Ostrer laboratory, high quality DNA was extracted from blood for all of subjects and lymphoblastoid cell lines were created. Following sample preparation using the Illumina library preparation kit, sequencing was accomplished using paired-end sequencing technology on an Illumina HiSeq2000 sequencer. The data from the Illumina sequencers was analyzed first using the Illumina sequencing data analysis pipeline for quality control. Paired end reads were aligned to the Human Reference Genome (NCBI Build 36) using the BWA software. Each alignment was assigned a mapping quality score by BWA, which is the Phredscaled probability that a read is misaligned. The basic functional annotation of SNPs/Indels is performed by ANNOVAR. The clinical features of these patients was consistent with those found by other studies on Ovotesticular DSD in South Africa and it also showed the same pattern of variation to the clinical features of Ovotesticular DSD from other parts of the world. Similar to previous South African studies, this study found no convincing gene mutations as the possible etiology of Ovotesticular DSD in South Africa. Whiles gene mutations such as duplication of SOX 9 have been found in patients with XX Ovotesticular DSD from outside South Africa, this study could not identify any such mutations. This further adds to the suspicion that the unique features of Ovotesticular DSD in South Africa suggests a different etiology from that of other parts of the world. In conclusion, the etiology of Ovotesticular DSD in South Africa still remains elusive. It is however possible that a genetic mutation may be found from a more critical analysis of the genome of the patients and their parents.